2018
DOI: 10.1142/s0217732318501614
|View full text |Cite
|
Sign up to set email alerts
|

Inflation with explicit parametric connection between general relativity and scalar–tensor gravity

Abstract: In this paper we consider the cosmological inflation with scalar-tensor gravity and compare it with standard inflation based on general relativity. The difference is determined by the value of the parameter ∆. This approach is associated with using the special ansatz which links a function that defines a type of gravity with a scale factor of the universe.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…: V,-vol ics in flat four-dimensional Friedmann-Robertson-Walker (FRW) space-time, which is sufficient for comparing such a models, since this type of geometry is the basis for constructing phenomenologically correct cosmological of models [53,54,61,62]. Also, this approach was used to analyze cosmological inflationary models based on the other modifications of Einstein gravity [60,63,64]. Thus, the application of the approach based on a connection between Einstein-Gauss-Bonnet gravity and General Relativity in relevant cosmological models makes it possible to evaluate the effects of the non-minimal coupling of a scalar field and the Gauss-Bonnet term.…”
Section: Introductionmentioning
confidence: 99%
“…: V,-vol ics in flat four-dimensional Friedmann-Robertson-Walker (FRW) space-time, which is sufficient for comparing such a models, since this type of geometry is the basis for constructing phenomenologically correct cosmological of models [53,54,61,62]. Also, this approach was used to analyze cosmological inflationary models based on the other modifications of Einstein gravity [60,63,64]. Thus, the application of the approach based on a connection between Einstein-Gauss-Bonnet gravity and General Relativity in relevant cosmological models makes it possible to evaluate the effects of the non-minimal coupling of a scalar field and the Gauss-Bonnet term.…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of scalar-tensor theories of gravity, one of which is the case of non-minimal coupling of a material scalar field and curvature. The construction of inflationary scenarios based on these theories of gravity has been carried out in many studies using exact and approximate solutions of the equations of cosmological dynamics [20,21,[25][26][27][28][29]. The main criterion for the correctness of the constructed models of the early universe based on the inflationary paradigm is the compliance of the spectral parameters of cosmological disturbances with the observational constraints obtained from measurements of the anisotropy and polarization of CMB [30].…”
Section: Introductionmentioning
confidence: 99%
“…The standard method for analysis of STG models and studying correspondence to GR is conformal transformations from Jordan frame to Einstein one [10,11]. The connection between STG and GR cosmological solutions without conformal transformations was considered in [12]. Also, the influence of non-minimal coupling on the deviation from de Sitter expansion is studied in [13] and it was shown that this approach leads to the models which have a good concordance to the observational constraints.…”
Section: Introductionmentioning
confidence: 99%